(untitled) (Indian Journal Of Clinical Practice, 2023)
Background: Vitamin B-complex aids in the development and maintenance of a healthy immune system and also helps to prevent or lessen various infections, especially cases of acute sickness like fever. This study investigates the opinions and experiences of doctors about the effectiveness and usefulness of the targeted vitamin B-complex combinations comprising of pyridoxine hydrochloride, cyanocobalamin, nicotinamide, chromium chloride, sodium selenite, L-lysine in hastening the recovery from acute diseases like fever and others. It offers insight on the perceived advantages, disadvantages and general efficacy of target vitamin B-complex combinations in comparison to other current medications by assessing doctors’ preferences, clinical observations and patient outcomes. Additionally, the study also outlines the role of selenium, chromium and L-lysine aiding in the faster recovery along with the targeted vitamin B-complex combination. Studies show that selenium supplementation can reduce mortality rates in viral infections, improve recovery rates in COVID-19 patients and improve the recovery rate. Chromium offers antioxidant properties, and influences immune response and hence helps in the faster recovery of several acute illnesses. Lysine serves as a pivotal building block for proteins, which in turn contribute significantly to the growth and restoration of bodily tissues following damage. Methods: The study was a retrospective study in July 2023 used a questionnaire-based survey to assess the efficacy and tolerability of vitamin B-complex combinations for faster recovery in acute illnesses, focusing on fever. The study used a validated questionnaire with 13 questions, and data was entered into a software database. Complete cases were analyzed, and missing data was excluded due to low occurrence. The final report was prepared after cleaning the data. Result: The study included 132 doctors from various medical specializations aimed to understand their perception and experience of using vitamin B-complex for faster recovery from acute illnesses. The most important factor contributing to choosing vitamin B-complex was the uses of micronutrients, which help produce red blood cells (40.2%), followed by use in treating mouth ulcers (31.1%) and are critical for pregnant ladies (28.8%). Antioxidants like selenium and chromium were found to be significantly effective (57.6%) for faster recovery in acute illnesses, while 39.4% considered them moderately effective. The study revealed that 88.6% of doctors considered the use of vitamin B-complex combination advantageous due to the presence of folic acid, L-lysine and selenium, and that 97.7% of doctors had a positive attitude about continuing to prescribe vitamin B-complex supplementation in the future. The study found that the current vitamin B-complex combination outperforms its competitors mostly (82%), especially in helping to recover from acute illnesses faster. It was also found to be friendly for the elderly, as no side effects were observed. Conclusion: Results suggest that the targeted vitamin B-complex combination can improve acute disease management and help health care professionals make informed decisions for optimal well-being. The findings contribute to a deeper understanding of the medical decisionmaking process and the nuanced considerations that impact the prescription of specific treatment options for acute illnesses.